cTAGE5 is essential for adipogenesis and adipose tissue development - Junwan Fan; Tiantian Ma; Xiaoping Ren; Zhilin Chang; Dan Zhang; Yi Wang; Shiyao Cheng; Xin Qi; Kehui Liu; Yan Wang; Yaqing Wang; Zhiheng Xu; et al. (Nature Communications)
Abstract White adipocytes serve as primary energy reservoirs and their malfunction is linked to different metabolic disorders, yet the mechanisms underlying cellular specialization, a critical step during adipogenesis remain unknown. Here, we reveal the indispensable role of cutaneous T-cell lymphoma-associated antigen 5 (cTAGE5) in adipocyte differentiation and maturation. Conditional deletion of cTAGE5 in adipocyte precursor cells (APCs), rather than mature adipocytes, results in progressive loss of white adipose tissue and death of mice. Mechanistically, cTAGE5 deficiency in APCs disturbs pro-insulin receptor (IR) processing and impairs insulin signaling, accompanied by significant down-regulation of actin cytoskeleton related genes and defect in cytoskeleton remodeling, alongside enhanced expression of proteins associated with lipid catabolic process and lipolysis in adipocytes. Importantly, inhibitors targeting actin polymerization and lipolysis effectively restore adipocyte differentiation capacity in cTAGE5-deficient APCs. Collectively, our findings demonstrate that cTAGE5 plays pivotal roles in adipogenesis and adipose tissue development.